Tata Kelola Olahraga Nasional: Perspektif Hukum dan Administrasi Negara - Tampubolon, Khairuddin; Elazhari, Elazhari; Alinur, Alinur; Mahuli, Jenda Ingan; Hiya, Nirmadarningsih (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
National sports governance in Indonesia is an important focus in building character, and discipline and achieving optimal achievements at the national and international levels. This article explains the importance of national sports governance from the perspective of state law and administration. The principles of good governance, such as accountability, transparency, community participation, fairness, and effectiveness, are the main foundation in national sports management. Clear regulations, including Law Number 3 of 2005 concerning the National Sports System, provide a strong legal basis. However, several challenges such as a legal framework that is not yet comprehensive, lack of coordination among stakeholders, limited resources, and abuse of authority need to be addressed. Improving regulations, strengthening coordination, increasing transparency, and accountability, and developing human resources in the field of sports are needed. This effort is expected to improve sports achievements and achieve better national sports development goals in the future.